1993
DOI: 10.1007/bf02251287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily SKF 38393, quinpirole, and SCH 23390 treatments on locomotor activity and subsequent sensitivity to apomorphine

Abstract: In three experiments, male Wistar rats (250-350 g) were injected (SC) daily with the D1-type dopamine receptor agonist, SKF 38393 (0.0, 4.0, 8.0, or 16.0 mg/kg), the D2-type dopamine receptor agonist, quinpirole (0.0, 0.3, or 3.0 mg/kg), and/or the D1-type dopamine receptor antagonist, SCH 23390 (0.0 or 0.5 mg/kg) for 8-10 days. After each daily injection, the rats were tested for locomotor activity in photocell arenas for 20 min. Following this subchronic pretreatment, all rats were challenged with the mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
6
31
0
Order By: Relevance
“…As noted previously, rats sensitized to quinpirole display cross-sensitization to cocaine and apomorphine (Horger and Schenk 1991;Mattingly et al 1993), and cross-sensitization between cocaine and apomorphine has also been reported (Kityakin 1994). The lack of cross-sensitization between 7-OH-DPAT and apomorphine and cocaine may be related to the apparent inability of repeated 7-OH-DPAT treatments to induce autoreceptor subsensitivity.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…As noted previously, rats sensitized to quinpirole display cross-sensitization to cocaine and apomorphine (Horger and Schenk 1991;Mattingly et al 1993), and cross-sensitization between cocaine and apomorphine has also been reported (Kityakin 1994). The lack of cross-sensitization between 7-OH-DPAT and apomorphine and cocaine may be related to the apparent inability of repeated 7-OH-DPAT treatments to induce autoreceptor subsensitivity.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, even doses of 7-OH-DPAT that acutely decreased dopamine synthesis did not significantly affect basal dopamine synthesis with repeated administration. Thus, the development of behavioral sensitization to high doses of 7-OH-DPAT, like tolerance to the initial locomotor inhibition, does not appear to be Bannon et al 1980;Brown et al 1985;Horger and Schenk 1991;Hoffman and Wise 1993;Kiyatkin 1994;Mattingly et al 1993;Rowlett et al 1991Rowlett et al , 1993Rowlett et al , 1995Szechtman et al 1994 related to changes in autoreceptor sensitivity. Interestingly, it has recently been reported that rats sensitized to the locomotor-activating effects of the D2-type agonist, bromocryptine, like 7-OH-DPAT, are not crosssensitized to cocaine (Hoffman and Wise 1993).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations